2020
DOI: 10.1093/ve/veaa076
|View full text |Cite
|
Sign up to set email alerts
|

The virome from a collection of endomycorrhizal fungi reveals new viral taxa with unprecedented genome organization

Abstract: Mutualistic plant-associated fungi are recognized as important drivers in plant evolution, diversity and health. The discovery that mycoviruses can take part and play important roles in symbiotic tripartite interactions has prompted us to study the viromes associated with a collection of ericoid and orchid mycorrhizal (ERM and ORM, respectively) fungi. Our study, based on high-throughput sequencing of transcriptomes (RNAseq) from fungal isolates grown in axenic cultures, revealed in both ERM and ORM fungi the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
113
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 100 publications
6
113
0
Order By: Relevance
“…This consistency in the viral sequences from different countries suggests that viruses with irregular genome structures are widely distributed, meaning that the event leading to the atypical structures did not occur locally. During revision of this manuscript, Dr. Turina and his colleagues reported a virus with a split RdRp that infects the ericoid mycorrhizal fungi Oidiodendron maius ( Sutela et al. 2020 ), which further supports our finding that AfuNV2 from three A. fumigatus strains and MoNV1 from a P. oryzae strain possess divided RdRp sequences on different genome segments.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This consistency in the viral sequences from different countries suggests that viruses with irregular genome structures are widely distributed, meaning that the event leading to the atypical structures did not occur locally. During revision of this manuscript, Dr. Turina and his colleagues reported a virus with a split RdRp that infects the ericoid mycorrhizal fungi Oidiodendron maius ( Sutela et al. 2020 ), which further supports our finding that AfuNV2 from three A. fumigatus strains and MoNV1 from a P. oryzae strain possess divided RdRp sequences on different genome segments.…”
Section: Discussionsupporting
confidence: 78%
“…A most intriguing finding was the presence of a divided RdRp gene. No examples like this irregular form have been reported in any other RNA viruses known to infect living creatures ( on the way of reviewing process, another example was reported ( Sutela et al. 2020 ), see below).…”
Section: Discussionmentioning
confidence: 98%
“… 2663f. Tulasnella ambivirus 4 28 30% 95% 5e-73 Armillaria borealis ambi-like virus 2 g AbAlV2 MW423806 A . borealis N40 4,529 49.1% 411,654f.…”
Section: Resultsmentioning
confidence: 99%
“…Our understanding of the virosphere has recently been revolutionized by high-throughput sequencing (HTS) studies, which have revealed many novel viruses representing yet unassigned virus groups related to but phylogenetically distinct from classified members of the orders Bunyavirales, Serpentovirales, Hepelivirales, Martellivirales, Tolivirales and Tymovirales , many of which have traditionally known to include only viruses that infect animals or plants ( https://talk.ictvonline.org/ictv-reports/ictv_online_report/ ). Furthermore, metagenomic studies have revealed the common occurrence of newly discovered evolutionary lineages of mycoviruses, such as the viral family Mymonaviridae in order Mononegavirales 26 , the viral family Botourmiaviridae in order Ourlivirales 27 , and the unclassified virus group tentatively named “ambiviruses” 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, PcoNSRV2 clusters with two unclassified fungal orthobunyaviruses, Botrytis cinerea orthobunya-like virus 1 (QKW91261) and Tulasnella bunyavirales-like 1 (QPB44676). The latter has an unprecedented 12 kb genome organization containing three ORFs, the largest one encoding the RdRp, the second largest ORF encoding an unknown protein with Tom22 motifs (mitochondrial translocase family) and the smallest ORF encoding a nucleocapsid protein [ 70 ]. This unique genome feature remains to be confirmed in PcoNSRV2 because no 5′ and 3′ RACE has been carried out yet.…”
Section: Resultsmentioning
confidence: 99%